Faktor-Faktor Risiko dan Protektif: Kecenderungan Penggunaan Kembali Pasien Penyalahguna Narkotika di Balai Besar Rehabilitasi BNN - Adhitya, Dipa Tri; Poerwandari, Elizabeth Kristi; Utami, Diah Setia (UI Scholars Hub, 2021)
Recovery does not go as expected due to risk factors that are more dominant than protective factors from patient abusers so that patient abusers have a tendency to reuse, these risk and protective factors can come from within the patient, family and environment. This study uses a qualitative design that uses in-depth interviews and focus group discussions (FGD). And the purpose of this study is to analyze the risk factors and protective tendencies of drug abuser patients reuse. The results showed that the external risk factors experienced by the informants were environmental factors, namely the influence of friends who used narcotics, the availability of narcotics in the informant's environment, conflicts in the family, negative communication patterns, weak parental supervision, low social ties. While the internal risk factors of the individual include: individual physiological factors, poor individual coping, poor impulse control and personality influences. Internal protective factors include: Positive individual perceptions, motivation/desire to recover, and individual religiosity. And external individual factors obtained are the existence of family support, the existence of bonds between family members, and the community in a positive environment. Keywords: Risk & Protective Factors, Rehabilitation, Relapse